ANALYSIS OF THE ERADICATION OF CORRUPTION IN INDONESIA: CHALLENGES AND EFFECTIVENESS OF REVERSING THE BURDEN OF PROOF - Lasmin Alfies Sihombing; Yeni Nuraeni (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Corruption in Indonesia is a serious problem that not only results in significant financial losses, but also has the potential to destroy social, economic, and democratic stability. Corruption has become a systematic crime, causing state losses of trillions of rupiah every year. This study aims to analyze various factors that affect the increase in corruption cases and the effectiveness of legal policies in eradicating them. Using a normative juridical approach, this study examines applicable regulations, including Law Number 20 of 2001 which regulates the reversal of the burden of proof in corruption cases. This study found that the implementation of a reverse evidentiary system can speed up the legal process and help uncover the material truth. However, the main challenges in eradicating corruption are low law enforcement, a permissive culture of law violations, and incompatibility of the law with the dynamics in the field. Therefore, periodic evaluation of regulations, strengthening the integrity of law enforcement officials, and strict supervision of the state budget are necessary. It is hoped that with these steps, efforts to eradicate corruption in Indonesia can be more optimal and have a positive impact on people's welfare.